Foliar nutrient uptake from dust sustains plant nutrition - A. Lokshin; A. Lokshin; D. Palchan; E. Golan; R. Erel; D. Andronico; A. Gross (Biogeosciences)
Mineral nutrient uptake from soil through the roots is considered the main nutrition pathway for vascular terrestrial plants. Recently, desert dust was discovered as an alternative nutrient source to plants through direct uptake from dust deposited on their foliage. Here we study the uptake of nutrients from freshly deposited desert and volcanic dusts by chickpea plants under ambient and future elevated levels of atmospheric CO2 through the roots and directly through the foliage. We find that within weeks, chickpea plants acquire phosphorus (P) from dust only through foliar uptake under ambient conditions and P, iron (Fe), and nickel (Ni) under elevated CO2 conditions, significantly increasing their growth. Using an additional chickpea variety with contrasting leaf properties, we show that the foliar nutrient uptake pathway from dust is facilitated by leaf surface chemical and physiological traits, such as low pH and trichome densities. We analyzed Nd radiogenic isotopes extracted from plant tissues after dust application to assess the contribution of mineral nutrients that were acquired through the foliage. Our results suggest that foliar mineral nutrient uptake from dust is an important pathway that may play an even bigger role in an elevated-CO2 world.